2015
DOI: 10.1111/1462-2920.13047
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic profiling of cellulosomal enzymes from the human gut bacterium, Ruminococcus champanellensis, reveals a fine‐tuned system for cohesin‐dockerin recognition

Abstract: Ruminococcus champanellensis is considered a keystone species in the human gut that degrades microcrystalline cellulose efficiently and contains the genetic elements necessary for cellulosome production. The basic elements of its cellulosome architecture, mainly cohesin and dockerin modules from scaffoldins and enzyme-borne dockerins, have been characterized recently. In this study, we cloned, expressed and characterized all of the glycoside hydrolases that contain a dockerin module. Among the 25 enzymes, 10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 54 publications
2
69
0
Order By: Relevance
“…Recent reports have delivered fresh insights into members of human gut Firmicutes which suggest a lifestyle specialized for degradation of insoluble fibre. Ruminococcus champanellensis, which is able to degrade microcrystalline cellulose (Chassard et al, 2012), encodes a system for binding and degrading cellulose via a protein complex known as a cellulosome (Smith and Bayer, 2013;Ben David et al, 2015;Moraïs et al, 2015), previously thought not to exist in the human gut microbiome. Interestingly, Ruminoccus bromii has also been found to mediate particulate starch degradation via a novel protein complex consisting of amylases with cellulosome-like dockerin modules that bind to a protein scaffold, which has been termed the amylosome (Ze et al, 2015).…”
mentioning
confidence: 99%
“…Recent reports have delivered fresh insights into members of human gut Firmicutes which suggest a lifestyle specialized for degradation of insoluble fibre. Ruminococcus champanellensis, which is able to degrade microcrystalline cellulose (Chassard et al, 2012), encodes a system for binding and degrading cellulose via a protein complex known as a cellulosome (Smith and Bayer, 2013;Ben David et al, 2015;Moraïs et al, 2015), previously thought not to exist in the human gut microbiome. Interestingly, Ruminoccus bromii has also been found to mediate particulate starch degradation via a novel protein complex consisting of amylases with cellulosome-like dockerin modules that bind to a protein scaffold, which has been termed the amylosome (Ze et al, 2015).…”
mentioning
confidence: 99%
“…For example, the abundance of Ruminococcus bromii in humans has been shown to be stimulated by a diet high in resistant starch (Walker et al , 2011). Moreover, some members are now considered as ‘keystone’ species (Ze et al , 2012; Moraïs et al , 2016), and several occur as prominent members of the ‘core gut microbiome’ found in a majority of humans (Qin et al , 2010). Aside from their presence in humans, other members are abundant and active in the degradation and fermentation of dietary polysaccharides in ruminant mammals (Leschine, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Some species are cellulolytic, including the rumen isolates R. flavefaciens and Ruminococcus albus (Hungate, 1957), and the recently described human isolate Ruminococcus champanellensis (Chassard et al , 2012), which is the only known bacterial species isolated from the human colon capable of degrading crystalline cellulose (Moraïs et al , 2016). Others are non-cellulolytic and utilize polysaccharides like resistant starches in the case of R. bromii (Ze et al , 2012), or selectively use various plant hemicelluloses in the case of Ruminococcus callidus (Lay et al , 2005) and ‘ Ruminococcus bicirculans ’ (Wegmann et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All dockerins from the R. champanellensis scaffoldins (eight in total) were tested, since they represent the main backbones of its cellulosome structures. The four additional selected dockerins belonged to the three dockerin groups (Groups 1, 2 and 3–4) of cohesin–dockerin interactions in this bacterium, as previously defined using bioinformatic‐based criteria (Ben David et al ., ; Morais et al ., ). ScaK, expressed as a full‐length protein (lacking the signal peptide), was able to interact with the ScaG and protein 3939 dockerins (Fig.…”
Section: Resultsmentioning
confidence: 97%